New routes for social justice: empowering individuals and innovative forms of collective action (London, 2017)
"Too late for therapy? Or, what is to be done about the relationship between citizens and states The state as a platform: Public policy in the digital age. Party policy and service delivery: Process vs outcome. How maybe not to die: Ideas for the rejuvenation of political. How can we better engage younger voters? Behavioural insights and the welfare state. ..."